(untitled) (SCHOLARS: Journal of Arts & Humanities, 2025)
This paper examines how Maya Angelou’s trauma, stemming from physical and psychological violence in her childhood, and how she expresses her resistance in her adulthood by writing her memoir, I Know Why the Caged Bird Sings. As she has tolerated unprotected situations since her conscious childhood phase, she is also deprived of legal rights and proper educational and medical opportunities. Her mother’s boyfriend not only rapes her, but also threatens to remain silent. She is warned not to disclose any information about rape, and she is also laughed at during the courtroom hearing of her rape case, suggesting the deprivation of legal rights. Further, she is denied access to quality educational and medical services. All these events shatter herself. Therefore, she incorporates all those traumatic experiences and writes her memoir in her adulthood as a part of healing, which helps her shape a dignified existence. To scrutinize the memoir, the researchers have chosen Kimberly Crenshaw’s intersectionality to analyze Angelou’s trauma, highlighting systemic failure, and Henke’s scriptotherapy to connect with her resilient situation that fosters healing. The thematic analysis of the data aims to find out Angelou’s hostile situations, their causes, and the actions taken for healing. This research significantly supports those researchers and academics who have contributed to trauma and healing.